Effect of Medical Image Fusion in the Treatment of Poststroke Limb Dysfunction with Acupuncture and Moxibustion of Traditional Chinese Medicine. - Feng, Aiping; Guo, Wanliang; Jia, Yong (BioMed Research International, 2022)
According to relevant data, the morbidity and mortality of strokes in China remain high. Without effective treatment, stroke morbidity and mortality will continue to rise, which may become the second leading disease in the world. With the nonstop advancement and improvement of clinical innovation in China, the death pace of stroke patients has dropped altogether. After clinical treatment, the patient actually showed a progression of sequelae, which made it challenging to work on the personal satisfaction of the patient. The purpose for this paper was to concentrate on the impact of medical image fusion in the treatment of poststroke appendage brokenness with TCM needle therapy. The related concepts of medical image fusion and the meaning of acupuncture and moxibustion in traditional Chinese medicine, stroke, and limb dysfunction were introduced. In this study, acupuncture and moxibustion were analyzed to explore the therapeutic effect of this type of therapy on upper extremity dysfunction caused by phlegm and blood stasis blocking collaterals and to provide a scientific method for the treatment and efficacy judgment of upper extremity motor dysfunction after stroke. Before the treatment measures were taken, there was no significant difference in the general data and all index scores between the two groups (P > 0.05), and there was no significant difference in the baseline data, reflecting high balance and comparability. In the following 3 months of treatment, the FMA score, NIHSS score, BI list, and VAS score of the two groups of patients were essentially not quite the same as those before treatment (P < 0.05). When treatment, there was a huge contrast between the trial group and the control group (P < 0.05). The finish of the trial in this paper is that needle therapy joined with pricking and measuring can essentially work on the engine capability of stroke patients with furthest point brokenness brought about by mucus and blood balance impeding securities.